Zu San Li Acupressure Method (ST 36) With Decreasing Nausea and Vomiting in Pregnant Women in the First Trimester at PMB Onni Dilla Roza Pekanbaru - Juli Selvi Yanti (Institute of Computer Science (IOCS), 2021)
Nausea and vomiting is a common symptom in the first trimester of pregnancy. Nausea and vomiting are a result of changes in the endocrine system that occur during pregnancy, especially the increase in the HCG hormone in pregnancy. One of the non-pharmacological treatment efforts that can be used to treat nausea and vomiting is acupressure therapy. This study aims to determine the effectiveness of the Zu San Li (ST 36) Acupressure Method on Reducing Nausea and Vomiting in First Trimester Pregnant Women at PMB Onni Dilla Roza in 2021. Types this research is quantitative analytic research. This research was conducted at PMB PMB Onni Dilla Roza. The population in this study were all first trimester pregnant women who visited PMB PMB Onni Dilla Roza. The sample in this study were first trimester pregnant women who experienced nausea and vomiting who were found at PMB PMB Onni Dilla Roza, totaling 15 people. Based on the results of research on the effectiveness of the Zu San Li (ST 36) acupressure method on reducing nausea and vomiting in pregnant women in the first trimester, there were 15 pregnant women who obtained the Mean Rank pretest and posttest results for the experimental group, the results of Zu San Li (ST 36) acupressure were effective. to decrease nausea and vomiting with p value 0.0001. It is hoped that PMB Onni Dilla Roza will be able to apply the Zu Sun Li (ST 36) acupressure method to pregnant women in order to help reduce nausea and vomiting experienced by pregnant women. Based on the results of research on the effectiveness of the Zu San Li (ST 36) acupressure method on reducing nausea and vomiting in pregnant women in the first trimester, there were 15 pregnant women who obtained the Mean Rank pretest and posttest results for the experimental group, the results of Zu San Li (ST 36) acupressure were effective. to decrease nausea and vomiting with p value 0.0001. It is hoped that PMB Onni Dilla Roza will be able to apply the Zu Sun Li (ST 36) acupressure method to pregnant women in order to help reduce nausea and vomiting experienced by pregnant women. Based on the results of research on the effectiveness of the Zu San Li (ST 36) acupressure method on reducing nausea and vomiting in pregnant women in the first trimester, there were 15 pregnant women who obtained the Mean Rank pretest and posttest results for the experimental group, the results of Zu San Li (ST 36) acupressure were effective. to decrease nausea and vomiting with p value 0.0001. It is hoped that PMB Onni Dilla Roza will be able to apply the Zu Sun Li (ST 36) acupressure method to pregnant women in order to help reduce nausea and vomiting experienced by pregnant women.